On-Road Study of Fatigue Management Strategies in Long-Haul Truck Drivers. (September 2014) - Sallinen, Mikael; Pylkkönen, Mia; Henelius, Andreas; Hyvärinen, Hanna-Kaisa; Puttonen, Sampsa; Virkkala, Jussi; Sihvola, Maria
The current study investigated what strategies long-haul truck drivers use to mitigate fatigue at the wheel. A group of 52 truck drivers participated in the study in which drivers' fatigue at the wheel was measured by a well-validated self-rating scale (the Karolinska Sleepiness Scale) and the use of fatigue countermeasures by a diary for a period of two consecutive workweeks including day and night-time trips. Results showed that the drivers more frequently used fatigue countermeasures while fatigued at the wheel but most of these countermeasures, with the exception of caffeine, can be regarded as inefficient (e.g., opening a window). The results indicate that long-haul truck drivers respond to fatigue at the wheel but the countermeasures they use are not optimal. It is likely that in addition to driver fatigue management training changes in shift and trip planning practices and sleeping facilities at rest stops are needed to improve the situation.